2016
DOI: 10.1088/0953-8984/28/13/134008
|View full text |Cite
|
Sign up to set email alerts
|

AFM-based tribological study of nanopatterned surfaces: the influence of contact area instabilities

Abstract: Although the importance of morphology on the tribological properties of surfaces has long been proved, an exhaustive understanding of nanopatterning effects is still lacking due to the difficulty in both fabricating 'really nano-' structures and detecting their tribological properties. In the present work we show how the probe-surface contact area can be a critical parameter due to its remarkable local variability, making a correct interpretation of the data very difficult in the case of extremely small nanofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…In this work, authors observed that relative humidity played a key role on the measurements, as also reported by Feiler et al [51]. In our experiments, we cannot rule out the possible formation of a thin water layer between the nanostructures patterns, which might interact during LFM scanning, as recently proposed as a hypothesis by Rota and collaborators for LFM measurements in nanostructured inorganic surfaces [52]. However, in this latter work, LFM was carried out using probes with a curvature radius higher than the mean size of the nanostructures, not allowing a local characterization of the material and making hard to conclude about the role of water within the nanostructured channels.…”
Section: Nanoscale Tribological Propertiessupporting
confidence: 51%
“…In this work, authors observed that relative humidity played a key role on the measurements, as also reported by Feiler et al [51]. In our experiments, we cannot rule out the possible formation of a thin water layer between the nanostructures patterns, which might interact during LFM scanning, as recently proposed as a hypothesis by Rota and collaborators for LFM measurements in nanostructured inorganic surfaces [52]. However, in this latter work, LFM was carried out using probes with a curvature radius higher than the mean size of the nanostructures, not allowing a local characterization of the material and making hard to conclude about the role of water within the nanostructured channels.…”
Section: Nanoscale Tribological Propertiessupporting
confidence: 51%
“…In addition, when the normal load increased, more silicon matrix was amorphized and thereby higher friction-induced hillocks were produced. The localized amorphous structure was expected to present lower density than crystal silicon, and hence piled up to form a hillock [58]. Similarly, the amorphization-dominated interaction may be the main contributor for the formation of friction-induced hillocks on other materials, such as glass and quartz [25,47,48].…”
Section: Mechanism For Friction-induced Hillock Formationmentioning
confidence: 99%
“…Besides the AFM, there are other experimental techniques to determine the force of friction at nanoscale, such as WENDELSTEIN 7-X, a test rig that allows the determination of sliding friction, 120 FFM, which is a modified form of AFM used specifically for friction measurements by lateral displacement, [121][122][123][124][125] etc.…”
Section: ! Omentioning
confidence: 99%